THE SCHOOL COUNSELOR AND MULTICULTURAL DIVERSITY AWARENESS IN THE VOLTA REGION OF GHANA - Sedem Nunyuia Amedome (Universitas Pendidikan Indonesia, 2023)
The skill of a counselor to work effectively with patients from varied cultural backgrounds is referred to as multicultural competency. Counselors and their clients may encounter cross-cultural differences in terms of race and other social variables; nonetheless, a culturally competent counselor does not see clients from different cultures negatively; otherwise, clients may assume the counselor is superior to them. This study investigates 60 counselors’ multicultural diversity knowledge and awareness in the domains of self-awareness, knowledge, skills, and their self-reported demographic characteristics using a standardized questionnaire. Though gender and age did not show any significant relationship with the counselors’ multicultural diversity knowledge and awareness, the number of years of working experience and the number of multicultural counseling courses a counselor took reported some relationship. The results and their implications are reported below for further consideration.